2016
DOI: 10.1007/s13300-016-0161-3
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Lipohypertrophy and Associated Risk Factors in Young Patients with Type 1 Diabetes: A Cross-Sectional Study

Abstract: IntroductionThe objective of this study was to investigate the frequency of lipohypertrophy (LH) and the associated risk factors in young patients with type 1 diabetes mellitus (T1DM).MethodsThis cross-sectional study was conducted on a sample of 174 patients with T1DM (aged 13–18 years) treated with multiple daily insulin injections for a minimum duration of 1 year. The study was performed at the Diabetes Treatment Center, Prince Sultan Military Medical City (Riyadh, Saudi Arabia), between July 2015 and Septe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
3
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 21 publications
5
51
3
9
Order By: Relevance
“…Though difference was not significant (p=0.273). The prevalence in this study is similar to a study by Al Hayek et al 16 However other studies found a prevalence of LH was high in type 2 diabetes patients. 7,8 Prevalence of LH was more in females compared to males.…”
Section: Discussionsupporting
confidence: 92%
“…Though difference was not significant (p=0.273). The prevalence in this study is similar to a study by Al Hayek et al 16 However other studies found a prevalence of LH was high in type 2 diabetes patients. 7,8 Prevalence of LH was more in females compared to males.…”
Section: Discussionsupporting
confidence: 92%
“…Interrater reliability of reviewers regarding study relevancy was high (Kappa = 0.86). Nine studies took place in Asia, 14 in Europe, and one each in North America, Africa and a mix of different countries. The median of the mean ages was 46 years (range 6.5–63.8 years), and the median percentage of males represented in the sample was 50% (range 27.3–59.1%).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the median number of participants per study was 228 (range 54–4352), the median of mean disease duration was 10.0 years (range 2.8–17.0 years) and the median of mean insulin treatment duration was 9.3 years (range 3.0–15.0 years). When evaluated by the modified Newcastle–Ottawa quality assessment criteria, out of 5 possible points, one study received 5 points, seven studies received 4 points, 14 received 3 points, three received 2 points and one received 1 point.…”
Section: Resultsmentioning
confidence: 99%
“…This higher BMI percentage may possibly be a result of the dramatic rise in the standard of living and the “Westernized” lifestyle habits adopted in Saudi Arabia. Unhealthy and unwise dietary choices coupled with reduced physical activity have produced this situation[12,18-20]. The growing “obesogenic” state that induced insulin resistance could account for the development of islet cell autoimmunity via different mechanisms.…”
Section: Discussionmentioning
confidence: 99%